The relationship between reading comprehension and reading strategy use among Malaysian ESL learners. - Zare, Pezhman; Othman, Moomala (Center for Promoting Ideas (CPI), USA, 2013)
The study was an attempt to find out the rate of recurrence of reading strategy use among Malaysian ESL learners. It also tried to figure out the possible relationship between reading strategy use and reading comprehension. Moreover, the study was after the influence of gender on the use of these strategies. Ninety five ESL learners participated in the study. A reading strategy inventory and a reading comprehension test were used to collect the required data. The data were analyzed through descriptive statistics to determine the frequency of strategies employed by the learners. Independent sample t-test was also employed to find out how the use of strategies varied according to gender. Moreover, Pearson coefficient correlation was used to discover the association between reading strategy use and reading comprehension achievement. According to the findings Malaysian ESL learners can be categorized as high strategy users. It was also revealed that significant differences exist between male and female language learners in the use of reading strategies. Furthermore, the use of reading strategies had a strong positive correlation with reading comprehension achievement.